Phase change energy storage composite material as well as preparation method and application thereof
By alternately setting the carbon film layer and the phase change material film layer in the phase change energy storage material and forming a spiral structure during the twisting process, the shortcomings of existing phase change energy storage materials in terms of thermal conductivity, leakage risk, energy storage density and structural stability are solved, and efficient thermal energy storage management and multifunctional applications of materials are achieved.
Patent Information
- Application Number
- CN202411748208.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-31
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Existing phase change energy storage materials have shortcomings in thermal conductivity, leakage risk, energy storage density and structural stability.
By alternately positioning the carbon film layer and the phase change material film layer, and oriented the carbon film layer in the circumferential direction during twisting, a helical structure is formed to encapsulate the phase change material to improve structural stability and prevent leakage, while increasing the energy storage density by increasing the thickness of the phase change material film layer.
It achieves high thermal conductivity, low leakage rate, high energy storage density and structural stability, and is suitable for energy storage systems, temperature control materials and thermal protection systems.
Smart Images

Figure CN119502476A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of phase change energy storage, and in particular to a phase change energy storage composite material and a preparation method and application thereof. Background Art
[0002] The high strength and stiffness of spiral materials make all-carbon spiral materials an ideal choice for reinforcement materials, which can significantly improve the mechanical properties of composite materials, including strength, stiffness and durability. At the same time, they also have excellent electrical and thermal conductivity. They have great potential in electronic, electrical and thermal management applications. The composite of spiral materials and phase change materials can significantly improve the electrical and thermal conductivity of the materials, thereby expanding the application range of composite materials, such as electromagnetic shielding, sensors and thermal conductive materials. In addition, the low density of composite spiral fibers makes them widely used in lightweight and multifunctional materials, such as aerospace, automotive, medical and energy.
[0003] Patent CN116768642A The present invention provides a spiral fiber-flexible substrate combined stretchable sensor and its preparation method and application. The spiral conductive fiber is fixed on the flexible substrate, and the flexible substrate is set to a local conductive structure. A conductive path is formed by combining the spiral conductive fiber and the local conductive flexible substrate. During the stretching process, different conductive paths are formed by utilizing the resistance difference between the spiral conductive fiber and the conductive part of the flexible substrate, and the current flow path is continuously changed, thereby changing the resistance value during the stretching process to achieve the sensing function.
[0004] Patent CN115323580B The present invention discloses a heat-driven deformation fabric based on super-helical composite fiber and its preparation method, the preparation method comprising the steps of: forming an organic polymer coating layer on the circumferential surface of the conductive fiber to obtain a composite fiber; twisting the composite fiber to obtain a super-helical composite fiber; weaving the super-helical composite fiber to obtain a heat-driven deformation fabric. The fabric can shrink in size under heat-driven conditions, so that the fabric structure becomes tighter, the fabric air permeability, moisture permeability, light transmittance, and perspective are reduced; after removing the heat drive, the fabric returns to its original size, the fabric structure returns to its original loose state, the size becomes larger, and the air permeability, moisture permeability, light transmittance, and perspective are restored.
[0005] However, existing phase change energy storage materials have shortcomings in thermal conductivity, leakage risk, energy storage density and structural stability. Summary of the invention
[0006] The first object of the present invention is to provide a phase change energy storage composite material with high heat storage coefficient, low leakage rate and three-dimensional thermal conductivity.
[0007] The second object of the present invention is to provide a method for preparing the phase-change energy storage composite material.
[0008] The third object of the present invention is to provide an application of the phase change energy storage composite material.
[0009] The present invention is achieved through the following technical solutions: A phase-change energy storage spiral composite material, wherein the spiral composite material is obtained by twisting a strip-shaped composite film; The composite film comprises at least one carbon film layer and at least one phase change material film layer; The carbon film layers and the phase change material film layers are arranged alternately, and the number of the carbon film layers is equal to the number of the phase change material film layers or the number of the carbon film layers is one more than the number of the phase change material film layers.
[0010] During the twisting, the twisting direction of the strip-shaped composite film is oriented along the circumferential direction of the carbon film layer; The carbon film layer includes a carbon nanotube film or a graphene film; The phase change material includes paraffin, fatty acid or polyethylene glycol.
[0011] The phase change material film layer is doped with a polymer elastomer; In the phase change material film layer, the weight ratio of the polymer elastomer to the phase change material is 1-3:7-9; The polymer elastomer includes a thermoplastic elastomer or a thermosetting elastomer; The thermoplastic elastomer includes polyurethane or olefin block copolymer methyl ester; The thermosetting elastomer includes dimethylsiloxane; The olefin block copolymer includes Infuse 9530, Infuse 9100, Infuse 9807, Infuse 9107 or Infuse 9817.
[0012] The width of the composite film is 5 to 20 mm; The thickness of the phase change material film layer is 50-100 microns.
[0013] The thickness of the carbon film layer is 5 to 10 microns; The thermal conductivity of the carbon film layer is 50-1000 W / (m·K).
[0014] The method for preparing the phase-change energy storage composite material comprises the following steps: The liquid phase change material is loaded on the surface of the substrate, and a phase change material film layer is obtained after cooling; The phase change material film layers and the carbon film layers are alternately stacked and then hot pressed to obtain a composite film; The composite film is cut and twisted to obtain the phase change energy storage composite material.
[0015] The preparation method of the phase-change energy storage composite material comprises the steps of adding a polymer elastomer into the phase-change material, melting the polymer elastomer and loading the polymer elastomer on the surface of the substrate. The melting temperature is the melting temperature of the polymer elastomer plus 20-50°C; The heating rate of the melting is 1-10°C / min; The melting holding time is 20 to 60 minutes.
[0016] The substrate includes copper foil; The surface of the substrate is also coated with a release agent; The release agent includes mineral oil.
[0017] The temperature of the hot pressing is 100-200°C.
[0018] The holding time of the hot pressing is 60 to 360 seconds.
[0019] The holding pressure of the hot pressing is 0.1-1 MPa.
[0020] The twisting rotation number is 50-200r.
[0021] The twisting time is 10 to 40 minutes.
[0022] The phase change energy storage composite material is used to prepare an energy storage system; or Used in the preparation of temperature control materials; or Used in the preparation of thermal protection systems.
[0023] The thermal protection system includes clothing integrated with the phase change energy storage composite material.
[0024] Compared with the prior art, the present invention has the following beneficial effects: The phase-change energy storage composite material provided by the present invention has high thermal conductivity, low leakage risk, high energy storage density and strong structural stability.
[0025] The preparation method of the phase-change energy storage composite material provided by the invention is simple and can be produced on a large scale.
[0026] The phase-change energy storage composite material provided by the present invention can be widely used in the preparation of energy storage systems, temperature control materials and thermal protection systems to achieve safe and efficient storage and conversion of energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A lateral SEM photograph of the phase change energy storage composite material prepared in Example 1 is shown; Figure 2A longitudinal SEM photograph of the phase change energy storage composite material prepared in Example 1 is shown. DETAILED DESCRIPTION
[0028] Traditional phase change materials have low heat transfer efficiency due to their low thermal conductivity, which in turn affects the efficiency of energy storage and release of the phase change material. At the same time, the phase change material will undergo a volume change during the phase change process. Therefore, during the melting or solidification process of the phase change material, the packaging structure of the material may rupture, resulting in leakage. The possible leakage problem not only reduces the energy storage efficiency, but also may cause pollution to the environment and equipment. In addition, it is difficult for phase change materials in the prior art to achieve high energy storage density, which limits its application potential in compact spaces. This is because energy storage density refers to the energy stored in a substance per unit mass or unit volume; traditional phase change composite materials usually add a larger mass percentage of thermal conductive materials in order to improve thermal conductivity, which leads to a decrease in the mass percentage of phase change materials in the composite material, which is manifested as a decrease in energy storage density.
[0029] The present invention provides a phase-change energy storage composite material to solve the problems of high thermal conductivity, high leakage risk and low energy storage density of the phase-change energy storage material disclosed in the prior art.
[0030] Specifically, the present invention provides a phase-change energy storage composite material, which is obtained by twisting a strip composite film. The strip composite film is composed of at least one carbon film layer and at least one phase change material film layer. The carbon film layer and the phase change material film layer are arranged alternately, and the number of carbon film layers is equal to the number of phase change material film layers or the number of carbon film layers is one more than the number of phase change material film layers. After twisting the carbon film layer in the circumferential direction, the phase change material will be sealed in a space formed by the twisting of the carbon film layer, which can enhance the structural stability of the composite material and enable it to withstand repeated phase change processes without losing its structural properties. At the same time, the phase change material is also encapsulated in the space, which effectively prevents the leakage of the phase change material and improves the sealing and safety of the material. At the same time, since the carbon film layer is very thin and the thickness of the phase change material film layer is adjustable, the alternating arrangement of the carbon film layer and the phase change material film layer and the increase of the phase change material film layer can increase the loading amount of the phase change material while maintaining the structural stability, thereby improving the overall energy storage density of the phase change energy storage composite material, thereby improving its application potential in compact space. Moreover, after twisting, the spiral structure formed by the carbon film layer achieves a high radial heat conductivity coefficient perpendicular to the axial direction of the composite material, thereby accelerating the transfer speed of the heat stored in the phase change material. At the same time, in the composite material, the contact area between the phase change material and the carbon film layer is large, which is also conducive to improving the heat conduction efficiency between the phase change material and the carbon film layer.
[0031] Specifically, when twisting, the twisting direction of the strip-shaped composite film is oriented along the circumferential direction of the carbon film layer; the carbon film layer is located at the outer layer of the phase change composite material, so that the phase change material is encapsulated in the spiral structure formed by the carbon film layer.
[0032] Preferably, the carbon film layer may be a carbon nanotube film or a graphene film. However, it is obvious that other types of high thermal conductivity carbon films may also be used to implement the present invention.
[0033] Preferably, the phase change material is paraffin, fatty acid or polyethylene glycol. Obviously, other types of phase change materials can also realize the present invention.
[0034] Furthermore, a polymer elastomer is doped into the phase change material film layer; due to the adsorption effect of the polymer elastomer on the phase change material, the structural stability of the phase change material can be improved, so that the phase change material always maintains a membrane structure during repeated phase changes, while further reducing the leakage rate of the phase change material in the phase change composite material.
[0035] Specifically, in the phase change material film layer, the weight ratio of the polymer elastomer to the phase change material is 1-3:7-9. Preferably, the polymer elastomer is a thermoplastic elastomer or a thermosetting elastomer; wherein the thermoplastic elastomer is preferably polyurethane or methyl olefin block copolymer; the thermosetting elastomer is preferably dimethylsiloxane; the olefin block copolymer is preferably Infuse 9530, Infuse 9100, Infuse 9807, Infuse 9107 or Infuse 9817. Olefin block copolymer (OBC) consists of hard segments and soft blocks, in which the hard blocks are aggregated into a dispersed phase and the soft blocks are aggregated into a continuous phase. The two are combined to form a three-dimensional network structure, in which the hard segments act as the connection points of the physical cross-linked network structure. The phase change material crystals are dispersed in the amorphous phase of OBC, and the volume growth of the phase change material during the melting process is constrained by the OBC network. Therefore, OBC can be used to limit the fluidity of the molten phase change material.
[0036] Furthermore, the width of the composite film can vary between 5 and 20 mm, the thickness of the phase change material film layer can vary between 50 and 100 microns, and the thickness of the carbon film layer can vary between 5 and 10 microns. By simply changing the preparation, the above dimensions can be regulated to obtain phase change composite materials of different specifications, thereby meeting their application needs in different fields.
[0037] Furthermore, any carbon film layer with a thermal conductivity between 50 and 1000 W / (m·K) can realize the present invention.
[0038] The present invention also provides a method for preparing the phase-change energy storage composite material. The method is simple to operate. First, the liquid phase-change material is loaded on the surface of the substrate, and the phase-change material film layer is obtained after cooling; then the phase-change material film layer is removed from the surface of the substrate, and then the phase-change material film layer and the carbon film layer are alternately stacked and hot-pressed to obtain a composite film; finally, the composite film is cut and twisted to obtain the phase-change energy storage composite material.
[0039] In order to better shape the phase change material after cooling, when making phase change energy storage composite materials, a polymer elastomer can be added to the phase change material and then melted, and then the phase change material can be loaded on the surface of the substrate.
[0040] Specifically, the melting temperature is set to a temperature range of 20-50° C. higher than the melting temperature of the polymer elastomer, so that the polymer elastomer can be fully melted and can be more easily mixed with the phase change material.
[0041] Setting the melting temperature rise rate to 1-10°C / min and keeping the temperature for 20-60min after reaching the melting temperature can ensure that the polymer elastomer is fully melted.
[0042] Preferably, the substrate comprises copper foil; the function of the substrate is to serve as a bottom pressure film, and therefore, the present invention can also be implemented by using other metal foils.
[0043] In order to facilitate the removal of the cooled phase change material, a release agent may be coated on the surface of the substrate; Preferably, the release agent may be mineral oil.
[0044] During hot pressing, the temperature of hot pressing can be set to 100-200°C. When the temperature reaches the set value, the pressure can be maintained at 0.1-1MPa for 60-360s.
[0045] When twisting, the twisting revolutions can be set to 50-200r, and the twisting time can be set to 10-40min. After twisting the composite film, a phase change energy storage composite material can be obtained, and at this time, the space formed by the carbon film layer will encapsulate the phase change material.
[0046] The invention also provides application of the phase-change energy storage composite material.
[0047] The phase-change energy storage composite material can be used to prepare an energy storage system. In the energy storage system, the composite material can effectively store and release thermal energy, absorb and release a large amount of heat within a certain temperature range through the phase change process of the phase change material, and realize effective storage and regulation of energy.
[0048] The phase change energy storage composite material can be used to prepare temperature control materials that can be used to adjust the indoor temperature or the temperature of electronic equipment. By adding phase change materials to building materials, indoor temperature fluctuations can be reduced, comfort can be improved, and energy consumption can be reduced. In electronic equipment, this material can be used as a thermal interface material to improve the temperature uniformity of the equipment, prevent overheating, and extend the life of the equipment. The phase change energy storage composite material can be used to prepare a thermal protection system. In a thermal protection system, the composite material can be used to protect equipment from extreme temperatures. By using phase change materials in key parts of the system, heat can be absorbed when the temperature rises to prevent the system from overheating, and heat can be released when the temperature drops to keep the system temperature stable.
[0049] Specifically, the thermal protection system may be clothing integrated with the phase change energy storage composite material.
[0050] The present invention is further described below in conjunction with specific embodiments.
[0051] Example 1 1. OBC and paraffin particles in a ratio of 2:8 were mixed by mechanical stirring, and the mixture was placed in a heating kettle. The heating kettle was heated to 150°C at a rate of 10°C / min, and then kept warm for 40 minutes. Mechanical stirring was performed during the heating and keeping warm process to obtain a blended solution A.
[0052] 2. Apply mineral oil on one side of the copper foil, place the copper foil on the coating machine, and adjust the coating distance of the coating machine scraper to 80μm. Pour solution A on the copper foil coated with mineral oil, start the coating machine, and apply solution A on the copper foil with the scraper. After cooling to room temperature, remove the formed film from the copper foil to obtain coating film B.
[0053] 3. The coated film B and the CNT film with a thickness of 8 μm are stacked up and down and placed in a hot pressing mold. The hot pressing equipment is heated to 150°C for hot pressing. The hot pressing pressure is 0.6 MPa and the hot pressing state is maintained for 60 seconds. After cooling to room temperature, the composite film C is taken out.
[0054] 4. Cut the composite film C into strips with a width of 20 mm, fix one end of the strip on the motor and the other end on the movable slider, adjust the twisting direction so that the surface with the composite film faces the inside of the spiral structure, start the motor for twisting, the twisting speed is 140 rpm, and the twisting time is 20 min, to obtain a fiber D with a spiral structure.
[0055] 5. Spread the spiral fiber D flatly into an oven for low-temperature heat treatment, raise the temperature to 60°C, and heat treat for 10 minutes. After cooling to room temperature, take out the fiber to obtain the final composite spiral fiber material.
[0056] Example 2 The difference between this embodiment and embodiment 1 is that in step 1, OBC and paraffin particles in a ratio of 3:7 are mixed by mechanical stirring, and the remaining steps and parameters are consistent with embodiment 1.
[0057] Example 3 The difference between this embodiment and embodiment 1 is that in step 1, OBC and paraffin particles in a ratio of 1:9 are mixed by mechanical stirring, and the remaining steps and parameters are consistent with embodiment 1.
[0058] Example 4 The difference between this embodiment and embodiment 1 is that in step 2, the coating spacing of the coating machine scraper is adjusted to 50 μm, and the other steps and parameters are consistent with embodiment 1.
[0059] Example 5 The difference between this embodiment and embodiment 1 is that in step 2, the coating spacing of the coating machine scraper is adjusted to 100 μm, and the other steps and parameters are consistent with embodiment 1.
[0060] Example 6 The difference between this embodiment and embodiment 1 is that in step 3, the coating film B and the CNT film with a thickness of 8 μm are stacked alternately up and down, and a layer of 8 μm CNT film is stacked on one side of the coating film B. The three-layer film with the coating film B in the middle and the CNT film above and below the coating film B is placed in a hot pressing mold, and the remaining steps and parameters are consistent with embodiment 1.
[0061] Example 7 The difference between this embodiment and embodiment 1 is that in step 3, the coating film B and the CNT film with a thickness of 8 μm are stacked alternately up and down, the stacking of the coating film B and the CNT film is repeated once, and the twice stacked films are stacked up and down to form a stacking pattern of a total of 4 layers of one CNT film and one coating film, and finally a layer of CNT film is stacked on the outermost coating film to finally form a 5-layer stacking structure of CNT film-coating film-CNT film-coating film-CNT film, and the 5-layer stacked film is placed in a hot pressing mold, and the remaining steps and parameters are consistent with embodiment 1.
[0062] Example 8 The difference between this embodiment and embodiment 1 is that in step 4, the composite film C is cut into strips with a width of 5 mm, and the other steps and parameters are consistent with those in embodiment 1.
[0063] Example 9 The difference between this embodiment and embodiment 1 is that in step 4, the twisting rotation number is 200 rpm, and the other steps and parameters are consistent with those in embodiment 1.
[0064] Example 10 The difference between this embodiment and embodiment 1 is that in step 4, the twisting rotation number is 50 rpm, and the other steps and parameters are consistent with embodiment 1.
[0065] Embodiment 11 The difference between this embodiment and embodiment 1 is that in step 3, the hot pressing equipment is heated to 100° C. for hot pressing and the hot pressing state is maintained for 360 seconds, and the remaining steps and parameters are consistent with embodiment 1.
[0066] Example 12 The difference between this embodiment and embodiment 1 is that in step 2, silicone oil is coated on one side of the copper foil, and the other steps and parameters are consistent with those in embodiment 1.
[0067] Embodiment 13 The difference between this embodiment and embodiment 1 is that in step 3, the hot pressing pressure is 1 MPa, and the other steps and parameters are consistent with embodiment 1.
[0068] Embodiment 14 The difference between this embodiment and embodiment 1 is that in step 3, the hot pressing pressure is 0.1 MPa, and the other steps and parameters are consistent with embodiment 1.
[0069] Embodiment 15 The difference between this embodiment and embodiment 1 is that in step 4, the twisting time is 40 minutes, and the other steps and parameters are consistent with embodiment 1.
[0070] Example 16 The difference between this embodiment and embodiment 1 is that in step 4, the twisting time is 10 minutes, and the other steps and parameters are consistent with embodiment 1.
[0071] Embodiment 17 The difference between this embodiment and embodiment 1 is that in step 3, the thickness of the CNT film is 10 μm, and the other steps and parameters are consistent with embodiment 1.
[0072] Embodiment 18 The difference between this embodiment and embodiment 1 is that in step 3, the thickness of the CNT film is 5 μm, and the other steps and parameters are consistent with embodiment 1.
[0073] Comparative Example 1 The difference between this comparative example and Example 1 is that in step 2, OBC and paraffin particles in a ratio of 1:20 are mixed by mechanical stirring, and other steps and parameters are consistent with Example 1.
[0074] Comparative Example 2 The difference between this comparative example and Example 1 is that there is no step 5, and the other steps and parameters are consistent with Example 1.
[0075] Comparative Example 3 The difference between this comparative example and Example 1 is that in step 2, solution A is directly poured onto the copper foil, and the other steps and parameters are consistent with those in Example 1.
[0076] Comparative Example 4 The difference between this comparative example and Example 1 is that in step 2, the copper foil is placed on the coating machine, and the coating spacing of the coating machine scraper is adjusted to 130 μm. The other steps and parameters are consistent with Example 1.
[0077] Comparative Example 5 The difference between this comparative example and Example 1 is that in step 2, the copper foil is placed on the coating machine, and the coating spacing of the coating machine scraper is adjusted to 30 μm, and the other steps and parameters are consistent with Example 1; Comparative Example 6 The difference between this comparative example and Example 1 is that in step 3, the hot pressing pressure is 1.5 MPa, and the other steps and parameters are consistent with Example 1; Comparative Example 7 The difference between this comparative example and Example 1 is that in step 3, the hot pressing pressure is 0.05 MPa, and the other steps and parameters are consistent with Example 1; In the present invention, the samples prepared in the embodiments and comparative examples can be tested by the following method, and the results are listed in Table 1: 1. Observe the front view and cross-section of the sample using a JSM-7610 scanning electron microscope from Japan Electron. Use the measurement function of the scanning electron microscope to measure the angle α (°) between the spiral knot and the horizontal line, the spiral fiber diameter a1 (μm), and the spiral knot width a2 (μm).
[0078] 2. Thermal conductivity is calculated from resistivity according to the formula K1=440000 / (ρ+258)-295, where K1 is thermal conductivity (W / (m·K)) and ρ is resistivity (μΩ·cm) measured by the circuit board four-point method.
[0079] 3. The radial thermal conductivity of the sample is obtained by heat flow method and is denoted as K2.
[0080] 4. Tensile strength test: Tested in accordance with standard ISO 11566:1996.
[0081] 5. Latent heat is obtained by DCS testing.
[0082] 6. Leakage rate test: take a section of composite spiral fiber as a sample and weigh it, recorded as m0 (g). Heat the sample in a 90℃ oven and weigh it every 2 hours, recorded as m n (g), fiber leakage rate (%) is calculated according to the following formula.
[0083] Leakage rate = [(m0-m n ) / m0]×100% Comparative Examples 3, 5, and 6 were not tested because a coating film could not be formed without using a release agent, the coating thickness was too small to be demoulded easily, and the hot pressing pressure was too high to cause the film to rupture.
[0084] Table 1: As can be seen from the embodiments, the phase change material is enclosed in a spiral structure, which can improve the latent heat and thermal conductivity of the composite material and enhance the temperature regulation ability. The spiral structure composed of carbonaceous material has flexibility and plasticity, and can provide good mechanical properties and shape controllability in the composite material. This can make the phase change composite material easier to prepare into various shapes and sizes, suitable for different application scenarios. And the presence of the spiral structure helps to accelerate the phase change process and the transfer of heat. The spiral structure also helps to increase the surface area of the material, and more heat can be transferred through the fiber surface, thereby improving the out-of-plane thermal conductivity. This structure can also make the phase change material absorb or release heat faster, improving its thermal efficiency. At the same time, the spiral fiber structure can provide stronger structural support and stability, help prevent the flow or overflow of the phase change material, increase durability and cycle stability, and facilitate long-term use and multiple cycles. A multi-layer carbonaceous film and a phase change material film are provided to form a multi-layer spiral structure in the composite material, which can further reduce the leakage rate of the phase change material. At the same time, this design can greatly increase the content of the phase change material in the composite material, thereby improving the heat storage capacity of the composite material. At the same time, the setting of multiple layers of carbonaceous film can also greatly improve the thermal conductivity of the composite material. The diameter of the composite material increases with the increase of the number of stacked layers. The carbon film layer and the phase change material film are alternately arranged. The more layers there are, the higher the tensile strength of the prepared spiral fiber.
[0085] In order to reduce the leakage rate of phase change materials, polymer elastomers are added to phase change materials. Polymer elastomers have excellent flexibility and toughness. After being added to phase change materials, the resulting blend is more likely to form a softer, easier-to-process film, which is conducive to subsequent processing into a spiral structure. In addition, polymer elastomers can increase the surface roughness of the membrane and improve the adhesion properties of the phase change material membrane, making it easier to combine with the carbonaceous membrane, so the leakage rate is low, the mechanical properties are good, and the morphological stability is good. The addition of polymer elastomers will make the composite material more stable in shape during processing or use, reduce the possibility of deformation and shrinkage, and the coating film is not easy to powder, thus having a long service life.
[0086] It can be seen from the data of Example 1, Example 2 and Example 3 that the content of paraffin directly affects the phase change temperature, latent heat, mechanical properties and stability of the composite material. Paraffin has low thermal conductivity, so the thermal conductivity decreases as the content of paraffin increases. The paraffin addition ratio in Example 3 is higher than that in Examples 1 and 2, and its brittleness increases and the tensile strength decreases. The appropriate paraffin addition ratio can make the leakage rate low and maintain good cyclicity. The reduction of paraffin content is accompanied by an increase in OBC content. OBC has excellent flexibility and toughness. Blends containing more OBC are more likely to form softer and easier-to-process films, which are conducive to subsequent processing into spiral structures. OBC can improve the surface roughness of the film, and the addition of an appropriate amount of OBC improves the adhesion properties of the film, making it easier to combine with the carbon film layer, but the thermal conductivity of OBC is lower than that of paraffin. The appropriate OBC and paraffin addition ratio can improve the good comprehensive performance of the material.
[0087] From the data of Example 1, Example 4 and Example 5, it can be seen that under the same preparation process, the coating thickness affects the diameter of the final spiral fiber and the overall content of OBC and paraffin in the spiral fiber. The thicker the coating thickness, the larger the spiral fiber diameter, the longer the distance perpendicular to the spiral fiber direction, the longer the length of the spirally wound film, and the longer the path along the spiral direction and perpendicular to the spiral fiber direction during the heat transfer process, so K1 and K2 are lower than the spiral fiber with a smaller diameter. Compared with the thinner coating thickness, the overall content of OBC and paraffin is higher in the thicker coating thickness, so the latent heat of Example 5 is higher than that of Example 4.
[0088] It can be seen from the data of Examples 1, 6 and 7 that the diameter of the spiral fiber increases with the increase in the number of stacked layers. The CNT film and the phase change material film are alternately arranged. The more layers there are, the higher the tensile strength of the prepared spiral fiber.
[0089] From the data of Example 1 and Examples 9, 10, 15, and 16, it can be seen that increasing the twisting speed or twisting time to a certain extent helps to enhance the cohesion of the yarn, prevent looseness, and form a stable spiral structure. This structure not only enhances the mechanical strength of the fiber, but also the tensile strength of Example 9 is higher than that of Example 10.
[0090] From the data of Example 1 and Examples 17 and 18, it can be seen that due to the existence of intrinsic thermal resistance and interface thermal resistance, strong phonon scattering will be induced, resulting in the thermal conductivity of the CNT film being generally one order of magnitude lower than that of the monomer CNT. When the thickness of the thermal conductive material increases, the thermal resistance value increases with the thickness. It is not a completely proportional linear relationship, but may be a curve relationship with a larger slope. Therefore, the thickness of the CNT film is proportional to its thermal resistance value. The thicker the material, the greater the thermal resistance, resulting in a decrease in thermal conductivity.
[0091] It can be seen from the data of Example 1 and Comparative Example 1 that OBC has good flexibility and toughness and can enhance the mechanical properties of the material. If the OBC content is too low, the flexibility of the spiral fiber will be reduced, resulting in a decrease in the tensile strength of the material. The addition of OBC improves the morphological stability of the composite material and reduces the possibility of deformation and shrinkage. Too low OBC causes morphological instability in the spiral fiber during processing or use, and the coating film becomes powdery, thereby affecting the service life of the material. At the same time, the reduction of OBC reduces the stability of paraffin, resulting in a narrowing of the phase change temperature range of the phase change material or a decrease in the phase change performance, and an increase in the leakage rate.
[0092] From the data of Example 1 and Comparative Example 2, it can be seen that the tensile strength, latent heat and thermal conductivity of the material after low-temperature heat treatment are better than those of the material without low-temperature heat treatment. This is because the low-temperature heat treatment process can repair defects such as cracks and fissures formed in the composite film during the twisting process into a spiral structure. During the coating, twisting and other processing processes, the phase change material film layer will produce defects such as cracks and fissures. These defects will form thermal bridges, reduce the thermal conductivity, and cause uneven heat conduction in the material, thereby reducing the overall thermal conductivity efficiency of the material. At the same time, the defects will also cause some areas of the phase change material to lose the characteristics of the phase change material. Low-temperature heat treatment can cause the phase change material layer to melt slightly for self-repair.
[0093] It can be seen from the data of Example 1 and Comparative Example 3 that if no coating agent is added during the coating process, the blend cannot be removed from the copper foil after coating and cooling, so a release agent must be added to the copper foil to facilitate later demolding.
[0094] It can be seen from the data of Example 1 and Comparative Examples 4 and 5 that when the phase change material film layer is too thick, problems such as uneven thickness, bending, and cracks are more likely to occur in thick coatings than in thin coatings. These problems will affect the flatness of the phase change material film. The twisting process is processed at room temperature. Paraffin is more brittle and hard than at higher temperatures. The overly thick phase change material film has more paraffin content than the thin phase change material film. The overly thick phase change material film has high overall brittleness, low flatness and high brittleness, resulting in a high degree of cracking during the spiral process. The overly thick phase change material film is not easy to spiral, and the prepared spiral fiber material has low thermal conductivity and tensile strength. The phase change material film layer is removed from the copper foil after hot pressing. When the phase change material film layer is too thin, the tensile strength of the phase change material film is too low, which easily causes the film to rupture, making it impossible to demold.
[0095] It can be seen from the data of Example 1 and Comparative Examples 6 and 7 that excessive hot pressing pressure during the preparation of the phase change material film can easily lead to the rupture of the phase change material film, thereby failing to form a composite film of the phase change material film and the CNT film. When the hot pressing pressure is too low, the contact degree between the phase change material film and the CNT film is low, the bonding strength of the composite film is low, and the composite film is delaminated and cracked during the twisting process to prepare the spiral fiber, resulting in a decrease in thermal conductivity and tensile strength, and an increase in leakage rate.
Claims
1. A phase-change energy storage spiral composite material, characterized in that: The spiral composite material is obtained by twisting a strip-shaped composite film; The composite film includes at least one carbon film layer and at least one phase change material film layer; the phase change material film layer is doped with a polymer elastomer; the carbon film layers and the phase change material film layers are alternately arranged, and the number of carbon film layers is equal to the number of phase change material film layers or the number of carbon film layers is one more than the number of phase change material film layers.
2. The phase change energy storage composite material according to claim 1, characterized in that: During the twisting, the twisting direction of the strip-shaped composite film is oriented along the circumferential direction of the carbon film layer; The carbon film layer includes a carbon nanotube film or a graphene film; The phase change material includes paraffin, fatty acid or polyethylene glycol.
3. The phase change energy storage composite material according to claim 1, characterized in that: In the phase change material film layer, the weight ratio of the polymer elastomer to the phase change material is 1-3:7-9; The polymer elastomer includes a thermoplastic elastomer or a thermosetting elastomer; The thermoplastic elastomer includes polyurethane or olefin block copolymer methyl ester; The thermosetting elastomer includes dimethylsiloxane; The olefin block copolymer includes Infuse 9530, Infuse 9100, Infuse 9807, Infuse 9107 or Infuse 9817.
4. The phase change energy storage composite material according to claim 1, characterized in that: The width of the composite film is 5 to 20 mm; The thickness of the phase change material film layer is 50-100 microns. The thickness of the carbon film layer is 5 to 10 microns; The thermal conductivity of the carbon film layer is 50-1000 W / (m·K).
5. The method for preparing the phase change energy storage composite material according to claim 1, characterized in that: The steps include: The liquid phase change material is loaded on the surface of the substrate, and a phase change material film layer is obtained after cooling; The phase change material film layers and the carbon film layers are alternately stacked and then hot pressed to obtain a composite film; The composite film is cut and twisted to obtain the phase change energy storage composite material.
6. The method for preparing the phase-change energy storage composite material according to claim 5, characterized in that: The method comprises the steps of adding a polymer elastomer into a phase change material, melting the polymer elastomer and loading the polymer elastomer on the surface of a substrate; The melting temperature is the melting temperature of the polymer elastomer plus 20-50°C; The heating rate of the melting is 1-10°C / min; The melting holding time is 20 to 60 minutes. The substrate includes copper foil; The surface of the substrate is also coated with a release agent; The release agent includes mineral oil.
7. The method for preparing the phase-change energy storage composite material according to claim 5, characterized in that: The temperature of the hot pressing is 100-200°C. The holding time of the hot pressing is 60 to 360 seconds. The holding pressure of the hot pressing is 0.1-1 MPa.
8. The method for preparing the phase-change energy storage composite material according to claim 5, characterized in that: The twisting rotation number is 50-200r. The twisting time is 10 to 40 minutes.
9. The use of the phase change energy storage composite material as claimed in claim 1, characterized in that: Used in the preparation of energy storage systems; or Used in the preparation of temperature control materials; or Used in the preparation of thermal protection systems.
10. The use of the phase change energy storage composite material according to claim 9, characterized in that: The thermal protection system includes clothing integrated with the phase change energy storage composite material.
Citation Information
Patent Citations
A helical carbon nanofiber / TiO2 composite material and application thereof
CN109103029A
Preparation method of multifunctional wearable twisted yarn
CN117488452A
Method for preparing graphene phase change composite heat dissipation film through rolling and hot pressing
CN117962455A
Carbon nanotube twisted yarn and method for producing the same
JP2011208296A